Characterization of Hepatitis B virus polymerase mutations A194T and CYEI and tenofovir disoproxil fumarate or tenofovir alafenamide resistance. Issue 1 (24th September 2020) - Liu, Yang; Chang, Silvia; Martin, Ross; Flaherty, John; Mo, Hongmei; Feierbach, Becket
Abstract: Both the A194T and a quadruple mutation CYEI (S106C, H126Y, D134E and L269I) in hepatitis B virus (HBV) polymerase reverse transcriptase domain (pol/RT) are suggested to be associated with treatment failure with tenofovir disoproxil fumarate (TDF). To further evaluate this assertion, the prevalence of these mutations at baseline as well as their development and/or loss during TDF and tenofovir alafenamide (TAF) treatment was analysed in 3886 patients enrolled in Gilead HBV clinical studies. In total, six out of 3886 (0.2%) patients carried the rtA194T mutation, while only 1 patient carried a triple CYE and 2 patients carried a quadruple CYEI mutation at baseline. All the patients harbouring rtA194T or CYE/CYEI at baseline achieved viral suppression by week 96 after TDF or TAF treatment. No patients developed an rtA194T mutation or > 1 substitution of CYEI, and the number of patients losing any substitutions of CYEI (n = 17) was similar to the number who developed a single substitution of CYEI (n = 32) during treatment. Phenotypic evaluation of the site‐directed mutant (SDM) panel containing these mutations with or without other resistance mutations did not demonstrate a significant shift in TFV and TAF potency in vitro. No evidence of rtA194T and CYEI conferring resistance to TDF or TAF was observed based on the treatment responses to TDF or TAF in patients with mutations at baseline, the lack of selection of mutations after starting TDF or TAF treatment and no change in susceptibility to TFV or TAF in vitro.